6-(Azaindol-2-yl)pyridine-3-sulfonamides as potent and selective inhibitors targeting hepatitis C virus NS4B. Issue 4 (15th February 2015) - Chen, Guangming; Ren, Hongyu; Zhang, Nanjing; Lennox, William; Turpoff, Anthony; Paget, Steven; Li, Chunshi; Almstead, Neil; Njoroge, F. George; Gu, Zhengxian; Graci, Jason; Jung, Stephen P.; et al.
Graphical abstract